Assessing Effectiveness of Animated Instructional Media on Academic Performance and Retention of Genetics Concepts - Faruk, Umar Ramatu; Aliyu, Faruku; Hassan, Lawal Zahriya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The present study was carried out to assess the effectiveness of animated instructional media on academic performance and retention of genetic concepts among senior secondary school on biology students in Sokoto State. Adopted through Quasi Experimental design involving pre-test, post-test and post-posttest on two equivalent groups as experimental and control, the population on the study was 10148 SS III Biology students. In this regard, four intact classes were chosen with sample size of 238 SSIII students. Genetic Concept Performance and Retention Test (GCPRT) was the instrument used for data collection. Animated Instruction Media was used as instructional material to teach the experimental group while demonstration method was used to teach the control group. Independent sample t-test was used to test the four (4) hypotheses formulated in the study. The esults obtained in this line of research revealed that there was a significant difference in the academic performance and retention ability between students taught using Animated Instructional Material and those taught using demonstration method. It was therefore recommended for other senior secondary school teachers to harness the considerable benefits of technology, particularly animations, in teaching genetics and other related concepts.Keywords: animated, media, academic performance, retention.